2002
DOI: 10.1002/jclp.10053
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing privileges: Grail for some practitioners, potential calamity for interprofessional collaboration in mental health

Abstract: The focus of this article is the probable consequences, in the event psychologists aggressively pursue prescription privileges (RxP), upon collaboration between psychologists and physicians. The case for RxP is briefly and critically summarized and the current state of collaboration between psychologists and medical professionals is reviewed. Data are presented from a recent small survey of clinical psychologists that support the following hypotheses: (1) psychiatrists and other medical professional receive a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…The article by Weene (2002), "The Psychologist's Role In The Collaborative Process Of Psychopharmacology," provided a number of positive aspects of collaboration and noted the assets psychologists bring to a collaborative model would also apply to prescribing psychologists. The article by Bush (2002), " Prescribing privileges: Grail for some practitioners; potential calamity for interprofessional collaboration in mental health" suggested collaboration may be what psychologists prefer. Weene (2002) noted that psychologists function in a multidisciplinary environment and make contributions that complement those of physicians, nurses, teachers, parents, employers, and lawyers.…”
Section: Adequacy Of Collaboration Between Physicians and Psychologistsmentioning
confidence: 41%
See 3 more Smart Citations
“…The article by Weene (2002), "The Psychologist's Role In The Collaborative Process Of Psychopharmacology," provided a number of positive aspects of collaboration and noted the assets psychologists bring to a collaborative model would also apply to prescribing psychologists. The article by Bush (2002), " Prescribing privileges: Grail for some practitioners; potential calamity for interprofessional collaboration in mental health" suggested collaboration may be what psychologists prefer. Weene (2002) noted that psychologists function in a multidisciplinary environment and make contributions that complement those of physicians, nurses, teachers, parents, employers, and lawyers.…”
Section: Adequacy Of Collaboration Between Physicians and Psychologistsmentioning
confidence: 41%
“…While Weene (2002) and Bush (2002) agreed on the assets of collaboration, Bush also reported the results of a small web-based survey to back up his arguments that collaboration is common and that psychologists are already an integrated part of the health care field. His survey also leads one to question the degree of interest in PPP outside of the officials at the APA, a point addressed in more detail by Hayes et al (2002).…”
Section: Adequacy Of Collaboration Between Physicians and Psychologistsmentioning
confidence: 41%
See 2 more Smart Citations
“…The RÂP proposal remains controversial within psychology and objections involve anticipated negative effects of the amount of training (Albee, 2002;Bush, 2002;Hayes & Heiby, 1996, 1998Hayes, Walser, & Bach, 2002;Heiby, 2002;Heiby et al, 2004;McFall, 2002;Pollitt, 2003;Sechrest & Coan, 2002;Wagner, 2002). Proponents of RÂP have observed that the major reason for the failure of most enabling legislation is concern over the quality of the APA model training (Fox et al, 2009), and the consumer protection reasons given in one governor's veto of an enabling bill supports this impression (Lingle, 2007).…”
Section: Context Of Evaluating Râp Trainingmentioning
confidence: 42%